2014
DOI: 10.1021/ac5002433
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Bifunctionalized by Chemiluminescence Reagent and Catalyst Metal Complexes: Synthesis and Unique Chemiluminescence Property

Abstract: Despite much progress in functionalized gold nanomaterial (GNMs), chemiluminescent (CL) functionalized GNMs with high CL efficiency are far from fully developed. In this work, we report a general strategy for the synthesis of gold nanoparticles (GNPs) bifunctionalized by CL reagent and catalyst metal complexes (BF-GNPs) by taking N-(aminobutyl)-N-(ethylisoluminol) (ABEI) as a model of CL reagents. The complexes of 2-[bis[2-[carboxymethyl-[2-oxo-2-(2-sulfanylethylamino)ethyl]amino]ethyl]amino]acetic acid (DTDTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 45 publications
2
58
0
Order By: Relevance
“…The CL spectrum of ABEI/Co 2+ /CS hydrogels with H 2 O 2 exhibited a peak centered at ~ 440 nm, as shown in Supplementary Fig. 3 , which was consistent with that of the CL reaction of ABEI with H 2 O 2 15 . These results demonstrated that the CL reaction of ABEI with H 2 O 2 was responsible for the light emission.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The CL spectrum of ABEI/Co 2+ /CS hydrogels with H 2 O 2 exhibited a peak centered at ~ 440 nm, as shown in Supplementary Fig. 3 , which was consistent with that of the CL reaction of ABEI with H 2 O 2 15 . These results demonstrated that the CL reaction of ABEI with H 2 O 2 was responsible for the light emission.…”
Section: Resultssupporting
confidence: 83%
“…When H 2 O 2 slowly diffuses to the active site, Co 2+ as a catalyst would react with H 2 O 2 to produce a highly reactive hydroxyl radical OH • , followed by the reaction with ABEI anion and HO 2 – to facilitate the formation of ABEI radicals and O 2 •– . Finally, ABEI radicals react with O 2 •– to generate strong CL emission 15 . Because of the slow diffusion rate of H 2 O 2 in hydrogels with high viscosity and micro/nano-sized pores, the CL reaction is a slow-diffusion-controlled process and could proceed for several days.…”
Section: Discussionmentioning
confidence: 99%
“…4B . It was found that maximum CL emission of ABEI/CuFe 2 O 4 was around 445 nm, which was consistent with that of ABEI-H 2 O 2 CL system, indicating that the CL emission of the nanomaterials was generated by the reaction of ABEI with H 2 O 2 [ 29 ].
Fig.
…”
Section: Resultsmentioning
confidence: 55%
“…3G). 41 It was also reported that the attachment of Co 2+ to a rigid polymer resulted in an increase in the catalytic activity and the stability of the catalyst 42. Thus, it is believed that Co 2+ coordinated by hydroxyl groups on the inside wall of the microbeads with amorphous multi-core structure exhibited outstanding heterogeneous catalytic activity on the CL reaction, leading to the enhanced CL emission.…”
Section: Resultsmentioning
confidence: 96%